2015
DOI: 10.1007/s10719-015-9597-3
|View full text |Cite
|
Sign up to set email alerts
|

Design and syntheses of hyaluronan oligosaccharide conjugates as inhibitors of CD44-Hyaluronan binding

Abstract: Hyaluronan (HA) is an integral component of the extracellular matrix. Its interactions with a cell surface receptor CD44 has been shown to play important roles in a variety of biological events including cell proliferation and metastasis. As multivalent CD44-HA binding is critical for downstream signaling, compounds that can selectively disrupt the complex formation of HA polysaccharide with CD44 can serve as useful probes of CD44 mediated cellular events as well as potential leads for novel therapeutics. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…In particular, our work shows why and how R41 is crucial in the recognition of HA in all the three binding modes of which one was detected previously by crystallography [ 10 ] and two were observed for the first time in our simulations. Our results expand the molecular-scale knowledge of the CD44–HA interplay and therefore have potential to facilitate the development of novel therapies against conditions such as the metastasis of tumors [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 66%
“…In particular, our work shows why and how R41 is crucial in the recognition of HA in all the three binding modes of which one was detected previously by crystallography [ 10 ] and two were observed for the first time in our simulations. Our results expand the molecular-scale knowledge of the CD44–HA interplay and therefore have potential to facilitate the development of novel therapies against conditions such as the metastasis of tumors [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 66%
“…An intralymphatic drug delivery method using an HA-cisplatin conjugate was proposed in breast cancer to preferentially treat at-risk regional lymph nodes and avoid systemic toxicities [267]. Furthermore, HA-based nanocarriers were investigated as drug vehicles for systemic targeting of CD44-overexpressed cancers [268, 269]. HA-coated superparamagnetic iron oxide nanoparticles conjugated anticancer drug doxorubicin was delivered at much higher levels and distributed wider in the tumor tissue than intravenously injected free doxorubicin, leading to significant reduction of tumor growth [270].…”
Section: Ha As Therapeuticmentioning
confidence: 99%
“…The increases in affinity seen here for the aminobenzoic acid-modified tetrasaccharides were similar to the findings of Lu and Huang (67), whose lead compound was a modified thiol glycoside attached to the closed reducing terminal ring of HA4 AN . In silico modeling (67) suggested that the m-benzyl phenyl moiety of the compound could fit into the hydrophobic pocket (consisting of Cys81, Tyr83, Ile92 and Cys101), within the HA binding groove of CD44 (31,67), π-π stacking against the tyrosine sidechain. Thus, the aromatic rings of the aminobenzoic acid moieties studied here could be involved in similar stacking interactions within this pocket, resulting in the improved affinities observed (see Figure 1).…”
Section: Discussionmentioning
confidence: 99%